Conservative management of twin pregnancies with one dead fetus: is it safe? - C. Gürkan Zorlu; Hakan R. Yalçin; Turhan Claglar; Oya Gökmen (Acta Obstetricia et Gynecologica Scandinavica)
Background. Fetal death in one of the twins is unusual and the management issue of such a condition is not straightforward. Methods. We reviewed the outcomes of nine twin pregnancies with one dead fetus in whom follow‐up period exceeded 3 weeks. Results. The twinning frequency was 8.9 per thousand deliveries and the frequency of subsequent antepartum death of one fetus was found to be 3.8%. The preterm birth rate was 45.5%and the survival rate was 90.1%. The perinatal mortality rate was 12%. Maternal clotting disorder was observed in one patient and treated successfully with heparin. Conclusions. We suggest that these patients are best managed conservatively unless further hazard to the fetus or mother appears.